2016
DOI: 10.3390/su8040378
|View full text |Cite
|
Sign up to set email alerts
|

European Pesticide Tax Schemes in Comparison: An Analysis of Experiences and Developments

Abstract: Policy measures are needed to reduce the risks associated with pesticides' application in agriculture, resulting in more sustainable agricultural systems. Pesticide taxes can be an important tool in the toolkit of policy-makers and are of increasing importance in European agriculture. However, little is known about the effects of such tax solutions and their impacts on the environment, farmers, and human health. We aim to fill this gap and synthesize experiences made in the European countries that have introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 19 publications
0
50
0
3
Order By: Relevance
“…For example, Vijftigschild and Oskam () show for the Netherlands that between 1980/81 and 1991/92, despite pesticide prices increased up to 32.5%, the pesticide demand increased by 20%, which would indicate a simple and crude elasticity of +0.63. In a similar vein, pesticides taxes have not necessarily led to sharp decreases in pesticide use, as observed in Sweden and Denmark under the former tax scheme, but, rather, to a substitution of products, as observed in Norway (Böcker and Finger, ).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…For example, Vijftigschild and Oskam () show for the Netherlands that between 1980/81 and 1991/92, despite pesticide prices increased up to 32.5%, the pesticide demand increased by 20%, which would indicate a simple and crude elasticity of +0.63. In a similar vein, pesticides taxes have not necessarily led to sharp decreases in pesticide use, as observed in Sweden and Denmark under the former tax scheme, but, rather, to a substitution of products, as observed in Norway (Böcker and Finger, ).…”
Section: Discussionmentioning
confidence: 77%
“…For instance, national action plans have been established in countries of the European Union and pesticide taxation schemes have been established in some European countries (i.e. France, Sweden, Norway, Denmark) (Böcker and Finger, ; Lefebvre et al ., ). There have also been recent discussions on an introduction of a taxation scheme in other European countries such as Belgium, the Netherlands and Germany (ARCADIS Belgium, ; Hof et al ., ; Möckel et al ., ,b).…”
Section: Introductionmentioning
confidence: 99%
“…Frequent, prophylactic, and sometimes superfluous insecticide applications add to the growers’ private costs and also have negative external effects due to detrimental impacts on the environment and human health [31]. Furthermore, consumer trust may be undermined in a time of growing awareness for health and environmental issues in the food chain [32,33]. …”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Other countries in Europe that have introduced pesticide taxes as part of a pesticide reduction plan include France, Norway and Sweden. However, an analysis of experiences and developments of these schemes has demonstrated that overall, the effectiveness of pesticide taxes is limited, but if tax on a specific pesticide is sufficiently high, application and associated risks are reduced significantly [25]. Additionally, in all of these countries, the stockpiling of pesticides in advance of tax introduction or increases was observed.…”
Section: Discussionmentioning
confidence: 99%